General approach for the determination of the magneto-angular dependence of the critical current of YBCO coated conductors. (15th December 2016) - Zhang, X; Zhong, Z; Ruiz, H S; Geng, J; Coombs, T A
Abstract: The physical understanding and numerical modelling of superconducting devices which exploit the high performance of second generation high temperature superconducting tapes (2G-HTS), is commonly hindered by the lack of accurate functions which allow the consideration of the in-field dependence of the critical current. This is true regardless of the manufacturer of the superconducting tape. In this paper, we present a general approach for determining a unified function I c ( B, θ), ultimately capable of describing the magneto-angular dependence of the in-field critical current of commercial 2G-HTS tapes in the Lorentz configuration. Five widely different superconducting tapes, provided by three different manufacturers, have been tested in a liquid nitrogen bath and external magnetic fields of up to 400 mT. The critical current was recorded at 90 different orientations of the magnetic field ranging from θ = 0°, i.e., with B aligned with the crystallographic ab-planes of the YBCO layer, towards ±90°, i.e., with B perpendicular to the wider surfaces of the 2G-HTS tape. The whole set of experimental data has been analysed using a novel multi-objective model capable of predicting a sole function I c ( B, θ). This allows an accurate validation of the experimental data regardless of the fabrication differences and widths of the superconducting tapes. It is shown that, in spite of the wide set of differences between the fabrication and composition of the considered tapes, at liquid nitrogen temperature the magneto-angular dependence of the in-field critical current of YBCO-based 2G-HTS tapes, can be described by a universal function I c ( f ( B ), θ), with a power law field dependence dominated by the Kim's factor B/B 0, and an angular dependence moderated by the electron mass anisotropy ratio of the YBCO layer.